Reverse osmosis for the treatment of well water and wastewater for reuse - A. Mélendez- Rivera; J. Musa-Wasil; D. Almestica-Martinez; K. Malave-Llamas (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: Freshwater is a scarce resource, constituting only 2.5% of Earth's total water. Approximately 90% of freshwater is concentrated near the South Pole of the Antarctic Circle, exacerbating its scarcity for living organisms. Industries such as pharmaceuticals, textiles, food production, and agriculture rely heavily on monthly freshwater supplies for their operations. Proper disposal of wastewater from these sectors is imperative to meet environmental standards. This study aimed to evaluate the effectiveness of reverse osmosis systems in treating well water for human consumption, examine the possibility of reusing reverse osmosis treated wastewater, and assess the feasibility of reducing freshwater consumption and wastewater generation.METHODS: The study used the qualitative and quantitative data obtained in 2018, 2019, 2022, and 2023 from the manufacturing industry in Guayama, Puerto Rico. Statistical analysis was confidently conducted using the Paired T-Test and Pearson correlation tests, with Minitab Statistical Software (Version 21.1.0) utilized for statistical analysis.FINDINGS: The results of this study showed that reverse osmosis is an effective system for treating well water for human use and enabling the reuse of wastewater after treatment. A total of 2,397,000 gallons of wastewater were treated and reused for cooling towers and boilers, representing the same amount of freshwater conserved and wastewater not discharged into the sewer system. The metrics analyzed were total organic carbon, conductivity, nitrate levels, and total aerobic microbial population. Total organic carbon in the samples ranged from 3 to 29 ppb. Conductivity was between 0.3 μS/CM and 1.0 μS/CM. Nitrate levels were all under 0.2 ppm (0.2 mg/l). Total aerobic bacteria counts were 0 cfu per milliliter. Regarding the feasibility of reusing wastewater post-reverse osmosis treatment, the findings showed decreased levels of anions and cations in the treated wastewater. Additionally, all reverse osmosis-treated well water samples tested in 2022 met the quality control laboratory criteria.CONCLUSION: The study confirms that the reverse osmosis system effectively purifies well water for human use and demonstrates the potential for repurposing treated wastewater. Furthermore, 2,397,000 gallons of treated wastewater were repurposed for cooling towers and boilers, conserving freshwater resources, and preventing the discharge of an equivalent volume of wastewater into the sewer system.